2016
DOI: 10.1002/app.44247
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of thermally expandable core–shell microcapsules using organic and inorganic stabilizers and their application

Abstract: Thermally expandable core–shell microcapsules (TEM) were fabricated with an organic steric stabilizer and an inorganic Pickering emulsifier. In order to fabricate a TEM, acrylonitrile (AN) and metacrylonitrile (MAN) were used as monomers. Halloysite nanotubes (HNTs) and poly(vinylpyrrolidone) (PVP) were used as the inorganic Pickering emulsifier and the organic stabilizer, respectively. The liquid hydrocarbon content in the core, and the thermal and expansion properties, of TEMs with two different emulsifiers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Thermal expansion microspheres (TEMs) are polymer particles with core-shell structure, which are generally composed of thermoplastic polymer shell encapsulated with low boiling hydrocarbons [1]. Upon heating, the polymer shell softens, and the vapor pressure generated by the internal blowing agent causes microspheres to expand, the diameter of the expanded microspheres can be increased by 3-5 times [2]. After cooling, the microspheres still can maintain its expanded state.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal expansion microspheres (TEMs) are polymer particles with core-shell structure, which are generally composed of thermoplastic polymer shell encapsulated with low boiling hydrocarbons [1]. Upon heating, the polymer shell softens, and the vapor pressure generated by the internal blowing agent causes microspheres to expand, the diameter of the expanded microspheres can be increased by 3-5 times [2]. After cooling, the microspheres still can maintain its expanded state.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the AN‐MAN combination, dramatic changes in the size were not detected. Previous research has shown that particle size varies with several parameters such as the presence of certain monomers and core materials . It has also been reported that preparation process parameters can influence the final capsule size and size distribution; the main factors are polymerization conditions such as polymer reaction temperature, chemical structure of shell materials, structure of the reactor, agitation speed, and pH .…”
Section: Resultsmentioning
confidence: 99%
“…The mixture was polymerized at 60 °C and 1500 rpm for 8 h. After polymerization, the particles were washed with water several times, and the suspending agent was removed from the particles by stirring with acetic acid. Finally, the resultant was filtered and dried at ambient temperature for 48 h . Dried FMs were mixed with epoxy resin in order to prepare the test specimens and conduct further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The results plotted in Figure 8 could provide an approach to obtain the encapsulated content of alkane. 25,29,35,40 However, this value of Group 2 could not be obtained from the T g curve in Figure 8(b). The larger particle diameter of Group 2 and the small volume of the crucible caused the overflow of expanded TEMs, which led to the rapid reduction in this curve.…”
Section: Encapsulated Content Of Alkane Of Temsmentioning
confidence: 91%